Green Marketing in Tourism Village Development; Marketing Mix - Rubiyatno Rubiyatno (Dinasti Publisher, 2025)
The application of the green marketing mix in tourism, especially in tourism villages, involves marketing strategies that consider aspects of environmental sustainability in the development, promotion, pricing, and distribution of tourism products in tourism villages. Tourism villages are tourism products that are developed based on the potential of the village, both in the form of community, nature, and culture as an identity that has tourist attractions. Previous research related to green marketing mix has not specifically examined the influence of green marketing mix on tourist interest in tourist villages. Therefore, research on the influence of green marketing mix on tourist interest in tourist villages still has a research gap that needs to be filled. This study aims to determine the influence of green marketing mix on visitor interest in tourist villages. The type of research used is survey research with a quantitative approach. The population in this study is all tourists who have visited tourist villages in the Special Region of Yogyakarta. The tourists who will be used as samples are tourists who visit the 5 best tourist villages in 2022 and 3 tourist villages that are among the top 75 of the 2023 Indonesian Tourism Village Award from the Special Region of Yogyakarta, with a total of 200 tourist respondents. The sampling technique used in this study is accidental sampling, which determines the sample based on chance, that is, anyone who happens to be willing to fill out the questionnaire can be used as a respondent. The data analysis used was Descriptive Analysis and Multiple Linear Regression Analysis and assisted by SPSS. The results show that not all elements of green marketing have a significant effect on Tourist Interest. Green Place and Green Promotion have proven to have a significant influence, showing that the aspect of environmentally friendly location and effective promotion is an important factor in attracting tourists. In contrast, Green Product and Green Price did not show significant influence, indicating that environmentally friendly products and price have not been the main factors in tourists' decisions to visit tourist villages.